KONTRIBUSI MAHASISWA DALAM PROGRAM KULIAH KERJA NYATA (KKN) DI KELURAHAN SEKARAN : PEMBUATAN PLANG PENUNJUK ARAH UNTUK PENINGKATAN INFRASTUKTUR LOKAL - Pratiwiningrum, Dwi; Givari, Iqbal; Pangestu, Dyah Felina (Abimanyu : Jornal of Community Engagement, 2024)
The problem that occurs in Sekaran Village is the lack of adequate facilities related to road signs. In addition, signposts must be made to make it easier for migrants and local communities to access tourist objects around Sekaran Village. The signboard installation program that will be carried out by the 16th MIT Community Service group at UIN Walisongo Semarang 2023 is carried out by making information signs indicating directions to one of the tourist attractions that are unknown to the people of Sekaran Village and people from outside the Sekaran Village area. The first step in this community service activity is to conduct a field survey or direct observation of the location where the sign will be installed, and conduct interviews with local residents in the area where the sign will be installed. After direct observation of the location where the signboard will be installed, the next step is to make the signpost by purchasing the required equipment. After the signboards were finished, then proceed with the painting. After the painting process was carried out, it was followed by the installation of the signboards which was carried out by representatives of KKN students and produced 4 signposts that would be installed at 4 predetermined location points to show the direction of the road to Sendang Nyai Ketrik. Keywords : Installation of signboards, Sekaran Village, Sendang Nyai Ketrik